The determinants of government bond yields: A comparative analysis of African, emerging and developed countries - Machethe, Tumelo (Department of Finance and Tax, 2024)
Debt is a critical source of finance for countries to fund their budget deficits and development objectives. However, high yields discourage the issuance of bonds by African economies and impose financial difficulties, thus hindering the necessary development of the continent. This study examines the determinants of government bond yields in Africa and provides a comparative analysis against other emerging and advanced countries. The 10-year government bond is used as a proxy for the bond yield and its determinants are examined over the period 2010 – 2019. The Fixed Effects panel data model with an adjustment for heteroskedasticity and cross-sectional dependence is used. The findings show that Gross Domestic Product (GDP) growth, government debt and the Federal Reserve fund rate have a significant impact on African government bond yields. In contrast, for other emerging and advanced economies, additional factors affect government bond yields including the current account balance, exchange rate, inflation and volatility. The results of this study have important policy implications for governments in Africa as increased knowledge of the determinants of government bond yields provides direction as to what policies they can focus on to aid in lowering yields. For example, given that GDP growth is found to be a significant determinant of African government bond yields, this means that governments must focus on building industries so that they produce more finished goods. Intra-Africa trade must be expedited to foster self-sufficiency of Africa and reduce reliance on trade with the big economies. These results also serve to raise awareness and entice global investors towards holding African country bonds.